Tobacco Use and Cardiovascular Diseases in Older Adults - María Gabriela Balarezo García; Karla Hurtado Serrano; Ximena Elizabeth Trujillo Romero (Medisur)
Foundation: in a context of growing concern about the cardiovascular health of the elderly population, it is relevant to explore the possible association between tobacco consumption and cardiovascular diseases. Objective: determine the relationship between tobacco consumption and the presence of cardiovascular diseases in older adults in a hospital in the province of Tungurahua, Ecuador. Method: a descriptive, cross-sectional study was carried out on older adults treated at a hospital in the province of Tungurahua, Ecuador, between July and December 2022. The selection criterion was based on the subjects being older adults of both genders, with ages equal to or greater than 65 years, with residence in the province of Tungurahua for at least the last five years. The study population was made up of 352 older adults and the sample was obtained through simple random probabilistic sampling and consisted of 184 individuals. The study variables were: presence of cardiovascular diseases, tobacco consumption, age and marital status. The technique used to collect the data was the survey. The data analysis was carried out using descriptive statistics and the correlation (Phi coefficient) between the variables. Results: of the 184 patients, 58.2 % were smokers and 57.6 % had cardiovascular diseases. The average age was 80.9. 46.2 % of the participants were married and 35.3 % were widowed. A moderate significant association was found between smoking and the presence of cardiovascular diseases in older adults (Phi coefficient = 0.342; p < 0.01). Conclusions: the existence of a moderate significant association was found between smoking and the presence of cardiovascular diseases in older adults from Tungurahua.